Development of a Compact Wide-Slot Antenna for Early Stage Breast Cancer Detection Featuring Circular Array Full-View Geometry - S. S. Tiang; M. S. Hathal; N. S. Nik Anwar; M. F. Ain; M. Z. Abdullah (International Journal of Antennas and Propagation)
A novel planar type antenna printed on a high permittivity Rogers’ substrate is proposed for early stage microwave breast cancer detection. The design is based on a p-shaped wide-slot structure with 50 Ω microstrip feeding circuit to eliminate losses of transmission. The design parameters are optimized resulting in a good reflection coefficient at −10 dB from 4.5 to 10.9 GHz. Imaging result using inhomogeneous breast phantom indicates that the proposed antenna is capable of detecting a 5 mm size cancerous tumor embedded inside the fibroglandular region with dielectric contrast between the target and the surrounding materials ranging from 1.7 : 1 to 3.6 : 1.